2010
DOI: 10.1074/jbc.m109.000695
|View full text |Cite
|
Sign up to set email alerts
|

Folding Study of Venus Reveals a Strong Ion Dependence of Its Yellow Fluorescence under Mildly Acidic Conditions

Abstract: Venus is a yellow fluorescent protein that has been developed for its fast chromophore maturation rate and bright yellow fluorescence that is relatively insensitive to changes in pH and ion concentrations. Here, we present a detailed study of the stability and folding of Venus in the pH range from 6.0 to 8.0 using chemical denaturants and a variety of spectroscopic probes. By following hydrogen-deuterium exchange of 15 N-labeled Venus using NMR spectroscopy over 13 months, residue-specific free energies of unf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 53 publications
0
33
0
Order By: Relevance
“…NMR HDX analyses of UCH-L1, -L3, and -L5 N240 were carried out in 20 mM Tris-HCl (pH 7.6), 100 mM NaCl at 25 °C, as described previously283358. The previously reported backbone assignments of UCH-L3 (BMRB accession number 15121)59 were used to confirm the assignments of the 15 N- 1 H correlations.…”
Section: Methodsmentioning
confidence: 99%
“…NMR HDX analyses of UCH-L1, -L3, and -L5 N240 were carried out in 20 mM Tris-HCl (pH 7.6), 100 mM NaCl at 25 °C, as described previously283358. The previously reported backbone assignments of UCH-L3 (BMRB accession number 15121)59 were used to confirm the assignments of the 15 N- 1 H correlations.…”
Section: Methodsmentioning
confidence: 99%
“…{ 1 H}- 15 N heteronuclear nuclear Overhauser effect (hetNOE) of HP0242 confirmed that all the four helices are highly ordered on the timescale of ps-ns (Figure S1). Given that the unfolding kinetics of HP0242 variants under native conditions are on the timescale of hours to days, we opted to examine the slow folding dynamics of HP0242 by native NMR hydrogen-deuterium exchange (HDX)161729 for slow-exchanging amide groups and phase-modulated clean chemical exchange (CLEANEX-PM)30 for fast exchanging amide groups, mostly the N-terminal region. The time constants of residue-specific amide HDX at pH 6.8 spanned from 10 2 to 10 6  minutes with those corresponding to the second helix (H2) being the slowest (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The rates at which the backbone amide protons exchange with bulk solvent are determined HDX2931 and CLEANEX-PM30. NMR HDX of wt and tandem HP0242 was carried out using the previously described protocol.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…32 Further, it was observed for YFP that the maturation of complements for BiFC is impacted around pH 7.2. 33 In our study, we observed that pH 7.4 and 60 mM NH 4 Cl seem to be suitable for the fluorophore maturation and therefore we suggest that the pH range of 7.4-8.0 may be optimal for detection of ribosome assembly defect using BiFC.…”
Section: Discussionmentioning
confidence: 99%